A facile room temperature method to recycle Cd from CdS. Issue 4 (April 2023) - Feng, Huazhang; Xu, Tingting; Zhu, Yuanmin; Chen, Yanping; Su, Jingyun; Ha, Enna; Jia, Ran; Zhang, Kan; Ma, Lei; Wang, Luyang
Abstract: Cadmium-based semiconductors have a wide range of applications in light-emitting, energy conversion, photodetection and artificial photosynthesis. With the concern about the potential toxicity of Cd, it is necessary to recycle the element from the Cd based semiconductors. Commonly, the precipitation of Cd cations with S 2− is deemed as the end point of recycling. However, actually, CdS is easy to be oxidized and released into the environment and accumulate in the food chain. It still remains challenges on how to refine the Cd element and convert it to the raw material. Herein, we demonstrate a facile room temperature method for recycling Cd from CdS. Cd can be produced from CdS within 3 h with the help of the lithium-ethylenediamine solution. DFT calculations further confirm that the high surface energy of (100) and (101) planes are selectively attacked by the solvated electrons in the solution, which is in good accordance with the XRD, STEM-HAADF and XPS characterizations. With a total recovery efficiency of 88%, Cd is successfully recovered from the CdS powder. This method provides a new perspective on the treatment of Cd-based semiconductor waste, which is of great significance for the recycling of cadmium metal.